MiR-657 Targets SRCIN1 via the Slug Pathway to Promote NSCLC Tumor Growth and EMT Induction. (17th August 2022) - Zhang, Yingqian; Yuan, Jiao; Guo, Mengfei; Xiang, Run; Wang, Xiang; Xie, Tianpeng; Zhuang, Xiang; Li, Qiang; Lai, Qi
Abstract : Background . MicroRNA- (miR-) 657 has been shown to regulate immunological and inflammatory activity, and it has also been defined to be dysregulated in both non-small-cell lung cancer (NSCLC) and hepatocellular carcinoma. The mechanistic role whereby miR-657 influences NSCLC progression, however, has yet to be clarified. Methods . miR-657 and SRCIN1 expression levels were assessed via qPCR in the cell lines and tissues of NSCLC. Besides, correlations between the levels of miR-657 and NSCLC patient pathological characteristics were examined, and the Kaplan-Meier approach was employed for the evaluation of the prognostic utility of miR-657 in these patients. Moreover, the Pearson correlation analyses and dual-luciferase reporter assessments were used for detecting interactive relationships between miR-657 and SRCIN1. In addition, CCK-8, EdU, and Transwell assessments were employed for the appraisal of the ability of miR-657/SRCIN1 to regulate NSCLC cell proliferation and invasion. Western blotting was employed for the assessment of the levels of NSCLC cell proteins associated with the epithelial-mesenchymal transition (EMT) that were influenced by miR-657. The nude mice xenograft tumor model is established to observe the effect of miR-657 on NSCLC growth in vivo . Results . NSCLC patient tissues and cell lines exhibited upregulated miR-657 expression that was closely related to tumor differentiation, lymphoid metastasis, and TNM stage. High levels of miR-657 were predictive of a poorer NSCLC patient prognosis, and overexpressing miR-657 resulted in the more rapid growth of NCI-H1650 and A549 cells, with a concomitant increase in their invasion. In addition, miR-657 overexpression raised the levels of Slug, N-cadherin, and Vimentin in these two cell lines while promoting E-cadherin downregulation. Dual-luciferase reporter assays confirmed that miR-657 was capable of binding to the SRCIN1 gene, and SRCIN1 expression levels were negatively associated with those of miR-657, indicating that it acts as a negative regulator of this gene. Knocking down SRCIN1 was capable to reverse the influences of miR-657 inhibitor treatment on NSCLC cell behavior. Finally, in vivo studies showed that miR-657 promoted NSCLC cell growth. Conclusion . The obtained findings illuminate that miR-657 can promote the growth of tumors and the induction of the EMT in NSCLC cells by targeting SRCIN1 expression and modulating Slug pathway activation, highlighting this pathway as a promising therapeutic target in cases suffering from NSCLC.